The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1007/s10038-005-0354-5
|View full text |Cite
|
Sign up to set email alerts
|

Association of VKORC1 and CYP2C9 polymorphisms with warfarin dose requirements in Japanese patients

Abstract: Warfarin is the most commonly used oral anticoagulant for treatment of thromboembolism, but adjustment of the dose appropriate to each patient is not so easy because of the large inter-individual variation in dose requirement. We analyzed single nucleotide polymorphism (SNP) genotypes of the VKORC1 and CYP2C9 genes using DNA from 828 Japanese patients treated with warfarin, and investigated association between SNP genotype and warfarin-maintenance dose. Five SNPs in VKORC1, 5¢ flankingÀ1413A>G, intron 1À136T>C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(80 citation statements)
references
References 20 publications
7
72
1
Order By: Relevance
“…[6][7][8][9][10][11][12] In recent years, Mushiroda, et al reported that the CYP2C9 and VKORC1 haplotype may affect the warfarin maintenance dose. 13) Our group has also shown that there are ethnic differences in terms of the genetic polymorphism of CYP2C9 and VKORC1, 14,15) which suggests that the optimal warfarin dose could vary between ethnicities.…”
mentioning
confidence: 86%
“…[6][7][8][9][10][11][12] In recent years, Mushiroda, et al reported that the CYP2C9 and VKORC1 haplotype may affect the warfarin maintenance dose. 13) Our group has also shown that there are ethnic differences in terms of the genetic polymorphism of CYP2C9 and VKORC1, 14,15) which suggests that the optimal warfarin dose could vary between ethnicities.…”
mentioning
confidence: 86%
“…Although most of the variability observed in patients' response to warfarin may be attributed to genetic varations in VKORC1 (Mushiroda et al 2006;Schwartz and Stein 2006) that functions to regenerate reduced vitamin K (Rost et al 2004;Li et al 2004), polymorphisms in GGCX have also been indicated to have some association with inter-individual variation in warfarin maintenance-dose requirement (Shikata et al 2004;Chen et al 2005;Loebstein et al 2005;Wadelius et al 2005;Herman et al 2006;Kimura et al 2007;Vecsler et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Xiaoying Lei, 1 Yanhai Guo, 1 Jianbin Sun, 1 Heping Zhou, 2 Yonglan Liu, 1 Ping Liang, 1 and Zhen Yan 1 * A few warfarin pharmacogenetic dosing algorithms have been proposed, based on multiethnic or homogeneous populations, to estimate warfarin therapeutic doses. However, it remains to be proven that which algorithm is accurate in predicting warfarin dose in Chinese people.…”
Section: Accuracy Assessment Of Pharmacogenetic Algorithms For Warfarmentioning
confidence: 99%
“…Recent pharmacogenetic studies showed that variations in genes, especially vitamin-K epoxide reductase complex subunit 1 (VKORC1) and cytochrome P450 family 2 subfamily C polypeptide 9 (CYP2C9), contributed significantly to differences in warfarin dose requirements among patients, along with clinical and demographic factors [2][3][4][5]. Subsequent to these investigations, in 2007 the US Food and Drug Administration added pharmacogenetic information to the warfarin product label, highlighting the benefits of genotyping individual patients to improve the initial estimate of a reasonable warfarin dose [6].…”
Section: Accuracy Assessment Of Pharmacogenetic Algorithms For Warfarmentioning
confidence: 99%
See 1 more Smart Citation